Rancang bangun media sosial instagram Perpustakaan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Padjadjaran - Nurulauni, Nadiah; Rizal, Edwin; Yanto, Andri (Faculty of Communication, Padjadjaran University, 2024)
The Library of the Faculty of Social and Political Sciences (FISIP) at Universitas Padjadjaran (Unpad) serves as a supporting facility for the academic community of FISIP Unpad. To disseminate information, the FISIP Library still relies on print media, which limits the scope of the information provided, resulting in suboptimal dissemination of library resources. Conversely, the need for information dissemination is significant, given that FISIP is one of the faculties with the largest number of study programs at Unpad. Considering this, the objective of this research is to design the Instagram social media platform as a dissemination medium for the FISIP Library at Unpad. The research employs a qualitative methodology utilizing action research as its approach. The dynamic process of action research begins with planning, followed by action, observation, and reflection. Data collection methods include interviews, observations, and documentation, with data analysis conducted through matrix tables. The results of the research are presented in the form of stages of action research, which consist of planning, action, observation, and reflection phases. The first stage involves developing a plan based on the existing conditions in the field, followed by the realization of the plan during the action phase. The outcomes of the action phase are then observed and reflected upon. Based on the results of the observation and reflection, improvements and optimizations are necessary, both in terms of information and social media utilization; thus, a second cycle is implemented to address these issues. The study encompasses two cycles of action research, each including the stages of action, observation, and reflection. The research resulted in the creation of a functional Instagram account for the FISIP Library at Unpad, which includes content that pertains to library-related information.